Efektifitas Pijat Woolwich Dan Rebusan Daun Katuk Terhadap Kelancaran ASI Pada Ibu Post Partum Di Puskesmas Bula Seram Bagian Timur Maluku 2022 - Febby Yanti Risakotta; Agus Santi Br Ginting; Ageng Septa Rini (STIKes Santa Elisabeth Medan, 2023)
Breast milk is a liquid that has a very complex content and is needed for a baby to optimize growth and development. Breast milk consists of several elements such as water, enzymes, nutrients, hormones, antibodies which are difficult for humans to imitate. The concentration of elements in breast milk is different for each mother, this is adjusted to the circumstances and needs of her baby. Breastfeeding is very important because it contains nutrients that are needed for optimal growth and development, for health and survival. The purpose of this study was to determine the effectiveness of woolwich massage and katuk leaf decoction on the smoothness of breastfeeding in post partum mothers at the Bula Seram Health Center in the eastern part of Maluku in 2022. This type of quantitative research used Quarsi Experimental with a two group only post-test approach, the sampling technique was total sampling as many as 36 samples with Wilcoxon analysis test. The results show that there is an effect of woolwich massage on the smoothness of breastfeeding, p value 0.04 and boiled katuk leaves on the smoothness of breastfeeding in post partum mothers at Bula Seram Health Center, East Maluku, 2022, p value 0.05. In conclusion, woolwich massage and katuk leaf decoction are effective in expediting breast milk, but to smooth milk production, woolwich massage can produce milk immediately when the intervention is given. The management of Woolwich massage therapy is more effective for post partum mothers to smooth breastfeeding. From the results of the study it is suggested that it can provide alternative solutions for postpartum mothers in dealing with a lack of milk production, in order to facilitate the production of breast milk in postpartum mothers at home